THE A STUDY OF THE RELATIONSHIP BETWEEN TEACHERS’ LEADERSHIP CAPACITY AND THEIR DECISION-MAKING STYLES IN JILIN ART PRIMARY SCHOOL JILIN PROVINCE, CHINA - Gong, Junlin; Ye, Yan (Scholar: Human Sciences, 2022)
The main purpose of this study was to determine the relationships between teachers’ perception of leadership capacity and their decision-making styles in a primary school in Jilin during the academic year 2019-2020. A total of 56 teachers from a primary school in Jilin were surveyed in this study. The main source of the data was a questionnaire that investigated teachers’ perceptions of their leadership capacities and decision-making styles. The collected data were analyzed using descriptive statistics and Pearson Product Moment Correlation. The study found that teachers’ leadership capacities from primary school were perceived as needed. There was a significant relationship between teachers’ perceived leadership capacities and their decision-making styles in a primary school in Jilin, China.